Purification, crystallization and preliminary X-ray crystallographic analysis of a methanol dehydrogenase from the marine bacterium Methylophaga aminisulfidivorans MP(T) - Choi, Jin Myung (International Union of Crystallography, 2011)

(untitled)
Methylophaga aminisulfidivorans MP(T) is a marine methylotrophic bacterium that utilizes C(1) compounds such as methanol as a carbon and energy source. The released electron from oxidation flows through a methanol-oxidizing system (MOX) consisting of a series of electron-transfer proteins encoded by the mox operon. One of the key enzymes in the pathway is methanol dehydrogenase (MDH), which contains the prosthetic group pyrroloquinoline quinone (PQQ) and converts methanol to formaldehyde in the periplasm by transferring two electrons from the oxidation of one methanol molecule to the electron acceptor cytochrome c (L). In order to obtain molecular insights into the oxidation mechanism, a native heterotetrameric α(2)β(2) MDH complex was directly purified from M. aminisulfidivorans MP(T) grown in the presence of methanol and crystallized. The crystal diffracted to 1.7 Å resolution and belonged to the monoclinic space group P2(1) (unit-cell parameters a = 63.9, b = 109.5, c = 95.6 Å, β = 100.5°). The asymmetric unit of the crystal contained one heterotetrameric complex, with a calculated Matthews coefficient of 2.24 Å(3) Da(−1) and a solvent content of 45.0%.